IPhone for dummies - Baig, Edward C. (--For dummies., 2009)
Explains how to use the portable electronic device to make and receive phone calls, set up iTunes and the iPod, take photographs, send and receive e-mail, browse the Internet, and play podcasts, music, video, and photograph slideshows.